Teacher observations of loneliness and ostracism among five-year-olds: Associations with social–emotional functioning, vocabulary, and language background - Salo, Anne-Elina; Upadyaya, Katja; Kalland, Mirjam; Hyttinen, Sami; Salmela-Aro, Katariina; Lerkkanen, Marja-Kristiina (Elsevier BV, 2026)
Being included in play and forming positive peer relationships are critical for children to meet their need to belong in early childhood education and care (ECEC). Loneliness and ostracism, then, threaten meeting this need. In this study, five-year-old children’s (N = 31,169) loneliness and ostracism were examined through ECEC teacher observations. About one-sixth of the children were evaluated as lonely and close to one-tenth as ostracized often to very often. Groups of children were then formed, based on different combinations in these threats to belonging: 1) rare threats (80.2%), 2) frequently lonely (rarely ostracized) (10.5%), 3) accumulated threats (7.7%), and 4) frequently ostracized (rarely lonely) (1.6%). Multinomial regression analysis with pairwise comparisons suggested differences between the groups in children’s social-emotional functioning, vocabulary, and language background but not in gender. It is vital to equip ECEC teachers with competencies to observe and address loneliness and ostracism, to build safe and inclusive peer communities for all children, and to develop children’s social-emotional skills. Implications for ensuring that every child can build peer relationships, access play, and learn to positively include their diverse peers are discussed.